Relationship Between Total Rewards Perceptions and Work Engagement Among Chinese Kindergarten Teachers: Organizational Identification as a Mediator - Ji, Dongying; Cui, Li (Frontiers in Psychology, 2021)
Kindergarten teachers’ engagement in work is influenced by many factors. Total rewards perceptions, as an individual’s evaluation of the rewards provided by the organization, may promote work engagement when it can meet their intrinsic and extrinsic work demands. To explore the relationship between kindergarten teachers’ total rewards perceptions and work engagement, and the mediating role of organizational identification, a survey was conducted among 1014 kindergarten teachers applying the Chinese versions of the Total Rewards Perceptions Scale for Kindergarten Teacher, Kindergarten Teacher Organizational Identification Scale, and Kindergarten Teacher Work Engagement Scale. The results showed that kindergarten teachers’ total rewards perceptions and its four factors were positively correlated with organizational identification and work engagement. Organizational identification was positively related to work engagement. Organizational identification partially mediated the relationship between total rewards perception and work engagement among kindergarten teachers. We discussed the result of the relationship between total rewards perceptions, organizational identification, and work engagement among Chinese kindergarten teachers.